A New Result for a Blow-up of Solutions to a Logarithmic Flexible Structure with Second Sound. (11th February 2021) - Merah, Ahlem; Mesloub, Fatiha; Boulaaras, Salah Mahmoud; Cherif, Bahri-Belkacem
Abstract : This paper is concerned with a problem of a logarithmic nonuniform flexible structure with time delay, where the heat flux is given by Cattaneo's law. We show that the energy of any weak solution blows up infinite time if the initial energy is negative.